Simple One-Pot Conversion of Alcohols into Nitriles - Shimojo, Hiroyuki; Moriyama, Katsuhiko; Togo, Hideo (Synthesis, 2013)
Various benzylic and primary alcohols were efficiently converted into the corresponding nitriles in good yields at room temperature by treatment with tert-butyl hypochlorite, diiodine, or 1,3-diiodo-5,5-dimethylhydantoin in the presence of (2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl (TEMPO), followed by treatment with diiodine and aqueous ammonia. The nitriles were obtained in good yields and high purities simply by extraction of the reaction mixture with chloroform and subsequent removal of the solvent.
Keywords: nitriles; alcohols